(untitled) (SAARC Journal of Agriculture, 2018)
Buffalo is considered the dairy animal for 21st century due to its higher adaptability and productivity in the changing climatic conditions. There is a large diversity in the buffalo genetic resources and South Asia is home of high yielding source promising buffalo breed of Murrah and Nail Ravi. South Asia is inhabitant of 151.49 million buffalo populations out of 194.29 million of global populations. Besides, about 79.74 % of Asia and 77.9 % of world buffalo populations are inhabitant in South Asian countries. During the last decade, the world buffalo population has been increased by approximately 1.49% annually. South Asia is currently producing 100.74 million metric tons of buffalo milk which is about 96.05 % of Asia and 93.19 % of world buffalo milk production. The share of buffalo milk is around 51.07% of the total milk production of the South Asia. The contribution of buffalo milk in India, Nepal and Pakistan are 51.2%, 66.6% and 59.5% respectively in total milk production. Among the South Asian countries, maximum milk is produced by India followed by Pakistan, Nepal, Bangladesh, Sri Lanka and Bhutan. The productivity of buffalo has been recorded 410 kg-1buffalo-1year, 1880 kg-1buffalo- 1year, 1934 kg-1buffalo-1year and 867 kg-1buffalo-1year, 508 kg-1buffalo- 1year in Bangladesh, India, Pakistan, Nepal and Sri Lanka respectively. Although most of the buffaloes are non-descript indigenous types and their production potential is not satisfactory. There are different production systems are prevailing such as zero input-low output, low input-medium output and high input-high output. Moreover, selective breeding for buffalo with the same breed under low input-medium output production system and grading up of non-descript buffaloes using improver breed/s under zero input-low output production system has been commonly practiced. The demand of milk has been increasing due to economic solvency and rapid pace of urbanization but most of the countries are deficit in production even it is challenging to meet the projected demand to achieve the SDG by 2030. To increase the productivity through genetic improvement of buffaloes could be important thrust areas to obtain projected demand of milk. Productive and reproductive efficiency can only be improved by adopting suitable breeding policies and good management practices. SAARC J. Agri., 15(2): 227-239 (2017)